2019
DOI: 10.1111/jipb.12822
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcited phytochrome B interacts with brassinazole resistant 1 to repress brassinosteroid signaling in Arabidopsis

Abstract: Photoreceptor phytochrome B (phyB) mediates a variety of light responses in plants. To further elucidate the molecular mechanisms of phyB-regulated hypocotyl elongation, we performed firefly luciferase complementation imaging (LCI) screening for phyB-interacting transcription factors (TFs). LCI assays showed that phyB possibly interacts with brassinazoleresistant 1 (BZR1), BZR2, AUXIN RESPONSE FACTOR 6 (ARF6), and several WRKY DNA-binding TFs in a red light-dependent manner. Furthermore, biochemical assays dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 50 publications
(81 reference statements)
1
41
0
Order By: Relevance
“…DELLA repression is alleviated by GA-mediated DELLA degradation in persistent shade conditions. Besides DELLAs, various active photoreceptors have also been shown to inhibit the activity of BZR1, ARF and PIF [37][38][39]. Active BZR1, ARF and PIF target many shared and unique target genes, including genes involved in auxin inactivation and transport, as well as gibberellin synthesis and cell growth [36,40].…”
Section: Photoreceptors To Sense Temperature and Light Quality Quantmentioning
confidence: 99%
See 1 more Smart Citation
“…DELLA repression is alleviated by GA-mediated DELLA degradation in persistent shade conditions. Besides DELLAs, various active photoreceptors have also been shown to inhibit the activity of BZR1, ARF and PIF [37][38][39]. Active BZR1, ARF and PIF target many shared and unique target genes, including genes involved in auxin inactivation and transport, as well as gibberellin synthesis and cell growth [36,40].…”
Section: Photoreceptors To Sense Temperature and Light Quality Quantmentioning
confidence: 99%
“…These transcription factors together with their DELLA repressor constitute the BZR-ARF-PIF/DELLA (BAP/D) module (Figure 1) [36]. Similar to PIF and ARF, the third TF of this group, BZR1, is also inactivated upon light-activation of phyB and cry [37][38][39].…”
Section: Photoreceptor Control Of the Bap/d Modulementioning
confidence: 99%
“…A group of SINAT E3 ligases, on the contrary, are involved in degrading nonphosphorylated BES1 protein in the light [86]. In addition to light-controlled protein abundance of BES1 and BZR1, recent studies demonstrated that light negatively regulates the transcriptional activity of BES1 and BZR1 [88][89][90]92]. When illuminated by red and blue light, respectively, phytochrome B (phyB) and cryptochrome 1 (CRY1) interact specifically with nonphosphorylated BES1 and BZR1.…”
Section: Lightmentioning
confidence: 99%
“…When illuminated by red and blue light, respectively, phytochrome B (phyB) and cryptochrome 1 (CRY1) interact specifically with nonphosphorylated BES1 and BZR1. This light-dependent interaction leads to the inhibition of BES1 and BZR1 DNA-binding activity and ultimately the expression of their target genes [88][89][90]92]. Moreover, blue light-activated CRY1 also interacts with BIN2 and thus enhances the interaction between BIN2 and BZR1.…”
Section: Lightmentioning
confidence: 99%
See 1 more Smart Citation